Validation of Sun Exposure Reported Annually Against Interim Self‐report and Daily Sun Diaries. (20th July 2017) - King, Laura; Xiang, Fan; Swaminathan, Ashwin; Dear, Keith; Harrison, Simone L.; van der Mei, Ingrid; Kimlin, Michael G.; D'Este, Catherine; Lucas, Robyn M.
Abstract: Data on personal sun exposure over a period exceeding the immediate past days or weeks are typically self‐reported in brief questionnaire items. The validity of such self‐reporting of longer term personal sun exposure, for example over a year, including detail on variation across seasons, has not previously been investigated. In a volunteer sample ( n = 331) of Australian adults aged 18 years and over, we assessed the 12‐month reliability of sun exposure reported separately for each season, and its accuracy compared to a daily sun diary in the same season. Seasonal time outdoors displayed fair‐to‐good reliability between baseline and end of study (12 months), with responses showing higher agreement at lower levels of time outdoors. There was good agreement for ranking of individuals' time outdoors with the daily sun diary data, although the actual diary time outdoors was typically considerably lower than the self‐reported questionnaire data. Place of residence, education, being a smoker, day of the week (i.e. working day vs nonworking day) and working mainly outdoors were significant predictors of agreement. While participants overestimated their actual time outdoors, the self‐report questionnaire provided a valid ranking of long‐term sun exposure against others in the study that was reliable over time. Abstract : We assessed agreement of a self‐reported time outdoors questionnaire administered annually using Bland–Altman plots. Responses were most consistent at lower levels of reported time outdoors. The mean difference is close to zero; however, differences increased with increasing time spent outdoors. This finding is consistent with further analysis in this article by season.